Penetapan dan Pembayaran Pajak Bumi dan Bangunan Perdesaan Perkotaan (PBB-P2) di BPPD Kabupaten Sidoarjo - Dewi Agustya Ningrum; Fitria Ulandari (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2021)
Sidoarjo Regency has nine types of taxes which are sources of income for the region. Forced payments to the nine types of taxes are carried out not solely for the inclusion of regional cash, but the funds collected from the tax payments will be made for development for the sake of harmony and leveling of the local economy. This tax collection is felt to be very burdensome to taxpayers due to lack of socialization so that understanding of on the benefits that taxpayers can be feel with tax contributions is less appreciated. Taxpayers are asked to take an active role in paying taxes, so that taxpayers truly understand the tax regulations on how the tax determination path is carried out, the mechanism of tax payments is carried out. Revenue generated from tax collection provides a very large role in regional income. Local governments need a plan or strategy to identify the linkages between the existence of hotels, restaurants, places of tourism or entertainment, billboards, street lighting, earth and buildings and those that have the potential to be further developed. Regional tax is a  tax contribution given to the regional government by a taxpayer based on the law, where the Regional Tax Service Office is the executor of the tax collection. Paying taxes can be said to play a role or participate in helping implement state tasks handled by the government. Revenue from local taxes and regional retributions is a reliable source of PAD revenue. In the collection of regional taxes and regional levies, of course in accordance with legal  regulations and laws that have been set.